Interplate deformation at early‐stage oblique subduction: 3‐D thermomechanical numerical modeling. Issue 7 (5th July 2016) - Malatesta, Cristina; Gerya, Taras; Crispini, Laura; Federico, Laura; Capponi, Giovanni
Abstract: Oblique subduction zones are complex settings where the simultaneous action of trench‐normal and trench‐parallel components of convergence can produce heterogeneous deformational pattern of the upper plate and affect the accretional/erosional behavior of the plate margin. Here we present three‐dimensional thermomechanical numerical models that highlight some processes occurring in the early history (15–20 Myr) of intraoceanic oblique subduction zones, which so far represent the less studied case. These models have been compared with a simulation of a slab sinking under a continental plate. We test subduction starting in oceans floored by two classes of lithosphere: layered (fast spreading oceans) and serpentinite rich (slow to ultraslow spreading oceans). Two main domains develop along the margin of both type of oceanic plates: (a) a domain with a mostly stable trench, a shortening upper plate, characterized by the formation of a topographic relief, and (b) a domain with retreating trench and extending upper plate. In general, we observed that varying the subduction obliquity, the margin could either (i) record an erosional to a balanced accretion/erosion regime or (ii) be characterized by a predominant balanced accretion/erosion regime. In both cases, even where the sediment amount in the trench is high, the upper plate experiences tectonic erosion. We suggest that the formation of topographic reliefs on the fore arc is possibly related to the low amount of sediment in the trench, affecting interplate friction and promoting the upper plate indentation against the slab. The Puysegur subduction zone and the central Andes can be possibly natural examples of such a regime. Key Points: We tested oblique subduction zones using 3‐D thermomechanical models On the upper plate the deformational pattern and topography vary along an oblique subduction Even when the sediment amount in the trench is high the upper plate undergoes tectonic erosion